ADDITION OF VITAMIN E IN SEMENLIFE® DILUENT ON QUALITY AND SHELF LIFE OF SPERMATOZOA OF LANDRACE PIGS - Sanjaya, Gede Putra; Bebas, Wayan; Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2023)
Artificial insemination in pigs in Indonesia still uses liquid semen. Therefore, specific media are needed to maintain the quality of pig spermatozoa. This study aims to determine the effect of adding vitamin E (a-tocopherol) to Semenlife ® (INTTEC) diluent on the quality and shelf life of spermatozoa of landrace pigs. The sample used was fresh semen which was collected using a mass technique taken from the UPTD. Regional Artificial Insemination Center, Livestock Breeding and Forage/Livestock Institute of Bali Province. A total of 24 samples consisting of 12 samples in the SemenLife ® (INTTEC) diluent and 12 samples in the SemenLife ® (INTTEC) diluent + vitamin E 400 µg/ml were stored at 15-18 o C. Observation of spermatozoa quality (viability and motility) and storage time was carried out for 120 hours with observations of spermatozoa quality under a microscope every 24 hours, then DNA fragmentation was tested using the Pocrine 8-Hydroxy-desoxyguanosine ELISA Kit. The graph results of Duncan's test showed that the addition of 400 µg/ml vitamin E had a significant effect on the quality of spermatozoa, especially in terms of motility which was maintained at 48 hours and the lowest DNA fragmentation occurred at 72 hours. Furthermore, the addition of vitamin E was not able to extend the shelf life of landrace pig spermatozoa in diluent. Where, there was a decrease in motility and an increase in DNA fragmentation, respectively at 72 and 96 hours, in viability the decrease occurred periodically from the 0 hour to 120 hours. From the results of the quality and shelf-life tests obtained, spermatozoa can then be tested by conducting a fertility test to find out whether the results obtained can increase litter size.